From Confirmation to Contention: Pragmatic Functions of 'Aywa' in Jordanian Spoken Arabic - Хаді Хамдан; Джихад Аль-Шуайбі; Ранія Зарур; Руба Аляфе; Руа Халіл (Психолінгвістика)
Purpose. This paper examines the pragmatic functions of the discourse marker aywa in Jordanian Arabic (JA) and its role in facilitating social and conversational dynamics among Jordanian speakers.